CAMPUR KODE DALAM YOUTUBE XAVEIRA PUTRI ANALISIS: SOSIOLINGUISTIK PADA INTERAKSI DIGITAL - Riantika Zahara (EduGrows: Education and Learning Review, 2025)
This study addresses a central issue in multilingual digital communication: how code-mixing practices are employed by diaspora content creators to construct identity and foster cross-cultural audience engagement. This problem is significant given the rising prevalence of translanguaging on social media, which is often understudied within contextualized sociolinguistic frameworks. The research examines the sociolinguistic dynamics of code-mixing in the YouTube content of Xaviera Putri, an Indonesian creator based in South Korea, to understand how multilingual practices shape digital interaction and transnational identity. Using a qualitative case study approach integrated with critical discourse analysis, the study analyzes 12 hours of video content (2022–2024) featuring 58 instances of code-mixing. Findings reveal three primary patterns: intra-sentential mixing (67%) used to preserve cultural concepts and fill lexical gaps; inter-sentential switching (22%) functioning as discourse organizers; and tag switching (11%) serving as politeness strategies. Thematic analysis identifies three key sociopragmatic functions: acting as a cultural broker, audience design for multilingual engagement, and identity negotiation within KAIST’s academic community. These results support translanguaging theory by demonstrating how hybrid language practices reconcile cultural authenticity with global accessibility. The study contributes to theoretical advancements in digital sociolinguistics and offers practical frameworks for content creators navigating multilingual digital ecosystems.